2-Formylpyrrole natural products: origin, structural diversity, bioactivity and synthesis. Issue 2 (24th July 2018) - Wood, James M.; Furkert, Daniel P.; Brimble, Margaret A.
Abstract : 2-Formylpyrroles constitute a large and growing family of bioactive Maillard reaction products found in food, traditional medicine and throughout nature. Abstract : Covering: up to April 2018 2-Formylpyrroles are ubiquitous in nature, arising from the non-enzymatic Maillard reactions of amines and sugars. Often confused for secondary metabolites, these Maillard products display interesting biological activities including hepatoprotective, immunostimulatory, antiproliferative and antioxidant effects. This review presents all 2-formylpyrrole natural products reported to date and identifies structural sub-classes for their categorisation. The origin, biological activity and chemical syntheses of these natural products are discussed herein.